Production and regulation of interleukin-1 family cytokines at the materno-fetal interface. (November 2017) - Scott, Louis M.; Bryant, Aled H.; Rees, April; Down, Billy; Jones, Ruth H.; Thornton, Catherine A.
Highlights: LPS modulates multiple IL-1 family cytokines from placenta, choriodecidua and amnion. IL-1β/IL-18 production is caspase-dependent; IL-1α production is calpain-dependent. Amnion has broadest responsiveness to IL-1 family members. Complex IL-1 family network at materno-fetal interface. Abstract: IL-1 family members regulate innate immune responses, are produced by gestation-associated tissues, and have a role in healthy and adverse pregnancy outcomes. To better understand their role at the materno-fetal interface we used a human tissue explant model to map lipopolysaccharide (LPS)-stimulated production of IL-1α, IL-1β, IL-18, IL-33, IL-1Ra, IL-18BPa, ST2 and IL-1RAcP by placenta, choriodecidua and amnion. Caspase-dependent processing of IL-1α, IL-1β, IL-18, and IL-33 and the ability of IL-1α, IL-1β, IL-18, and IL-33 to regulate the production of IL-1RA, IL-18BPa, ST2 and IL-1RAcP was also determined. LPS acted as a potent inducer of IL-1 family member expression especially in the placenta and choriodecidua with the response by the amnion restricted to IL-1β. Caspases-1, 4 and 8 contributed to LPS-stimulated production of IL-1β and IL-18, whereas calpain was required for IL-1α production. Exogenous administration of IL-1α, IL-1β, IL-18, and IL-33 lead to differential expression of IL-1Ra, IL-18BPa, ST2 and IL-1RAcP across all tissues examined. Most notable were the counter-regulatory effect of LPS on IL-1β and IL-1Ra in the amnion and the broad responsiveness of the amnion to IL-1 family cytokines for increased production of immunomodulatory peptides and soluble receptors. The placenta and membranes vary not only in their output of various IL-1 family members but also in their counter-regulatory mechanisms through endogenous inhibitory peptides, processing enzymes and soluble decoy receptors. This interactive network of inflammatory mediators likely contributes to innate defence mechanisms at the materno-fetal interface to limit, in particular, the detrimental effects of microbial invasion.